Lymph node transfer using the middle jugular lymph node flap: Anatomical study and a report of two cases - Fumio Onishi; Bien-Keem Tan (JPRAS Open)
Background: The middle jugular region is a potential donor site for harvesting lymph nodes for vascularized lymph node transfer. The clinical outcome of lymph node flap is related to the number of lymph nodes contained therein and the integrity of their blood supply. Thus, in this study, we aimed to clarify the vascular anatomy of the middle jugular lymph node flap and explore its potential clinical applications in lymphedema treatment. Methods: We dissected nine cadaveric hemi-necks to study the middle jugular lymph nodes, delineating their blood supply, and their relationship to critical structures in the neck. The flap was clinically used based on the anatomical findings. Results: In the cadaveric study, an average of two lymph nodes were found in the middle jugular region. The lymph nodes were supplied by various branches of the superior thyroid artery, including the sternocleidomastoid artery (73%), superior laryngeal artery (20%), and a direct branch of the superior thyroid artery (7%). The hilar veins draining the flap consisted of those draining into the facial vein (40%), direct tributaries into the internal jugular vein (13%), and the superior thyroid vein (27%). Based on our anatomical findings, we could successfully apply middle jugular lymph node transfer in clinical cases with extremity lymphedema. There were no major complications during the follow-up period. Conclusion: The middle jugular region was a favorable donor site for lymph node transfer. Surgical access is straightforward and the nodes, if visualized, are easily dissected. The superior thyroid artery is a reliable pedicle for the flap.